Performance of Kampung Unggul Balitnak (KUB) Chickens with the Additions of Soya Flour in the Diet - Susan Mokoolang; Agustriyanto Abudi; Ramlan Pomolango; Fahrullah Fahrullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Ayam Kampung Unggul Balitnak (KUB) is the result of selecting native Indonesian kampong chicken strains for six generations that have advantages in terms of maintenance due to the level of feed consumption that is less. The aim of this research was to the effect of soybean flour on the performances of Balitnak Superior Kampong Chicken (KUB). This study used a completely Randomised Design consisting of 5 treatments and 4 replicates. The treatments consisted of T1: basal + 0% soya flour; T2: basal + 2,5% soya flour; T3: basal + 5% soy flour; T4: basal + 7.5% soya flour and T5: basal + 10% soya flour. The results showed that the use of soya flour in the ration of KUB chickens gave an increase in ration consumption, weight gain and could increase the efficiency of ration use. The best concentration of soya flour in the KUB chicken ration was 10%.